The Influence of Financial Literacy, Financial Self-Efficacy and Locus of Control on the Financial Behavior of Ciputra University Students - Dewi, Liliana; Sandriana, Rachiel (Dinasti Publisher, 2025)
This research aims to raise financial awareness and the importance of Financial Literacy, Financial Self-Efficacy, and Locus of Control towards Ciputra University students’ Financial Behavior. This study could act as a guide for students to increase their financial management skills and help them in the long run to achieve their financial goals. This is a quantitative study aimed at determining the effectiveness of independent variables such as Financial Literacy, Financial Self-Efficacy, and Locus of Control towards the dependent variable which is Financial Behavior at Ciputra University. The data collection method that is used for this study is a questionnaire with a Likert scale. Active students of the Ciputra University class of 2021 were used as the population and the purposive sampling method as the sampling technique that is used. The result of this study is that there is a significant and positive relationship between financial literacy and financial self-efficacy in the financial behavior of Ciputra University students. On the other hand, locus of control may have a positive effect on financial behavior but is not significant in the financial behavior of Ciputra University students.